Attitudes of Academic Library Managers towards Factors Affecting Information Needs Assessment - Mohammad Reza Davarpanah; Rahmatollah Fattahi; Rahmat Poormousa (Iranian Journal of Information Processing & Management, 2014)
A periodic information needs assessment in libraries and information centers will allow libraries to focus on providing access to the most appropriate resources for specific groups and increase users satisfaction and library effectiveness. The present research paper, which is an applied survey, focuses on the subjects’ attitude towards factors affecting information needs assessment in academic libraries. Research population included 190 subjects from 29 medical and non-medical academic libraries who were asked to fill-in a research-made questionnaire. The results showed that 70 percent of the surveyed libraries had never undertaken a systematic information needs assessment. Some of the significant factors affecting information needs assessment were: managerial commitment to identifying users’ information needs, postulation of user needs, managing s resistance to change, paying no attention to reality and policy. The tests showed meaningful differences among the subjects attitudes relating to their demographic variables; also the test indicated no significant differences between the attitudes towards the barriers of information needs assessment.